Household workers unite: the untold story of African American women who built a movement - Nadasen, Premilla (Boston, Ma., 2016)
"Telling the stories of African American domestic workers, this book resurrects a little-known history of domestic worker activism in the 1960s and 1970s, offering new perspectives on race, labor, feminism, and organizing. In this groundbreaking history of African American domestic-worker organizing, scholar and activist Premilla Nadasen shatters countless myths and misconceptions about an historically misunderstood workforce. Resurrecting a little-known history of domestic-worker activism from the 1950s to the 1970s, Nadasen shows how these women were a far cry from the stereotyped passive and powerless victims; they were innovative labor organizers who tirelessly organized on buses and streets across the United States to bring dignity and legal recognition to their occupation. Dismissed by mainstream labor as “unorganizable,” African American household workers developed unique strategies for social change and formed unprecedented alliances with activists in both the women’s rights and the black freedom movements. Using storytelling as a form of activism and as means of establishing a collective identity as workers, these women proudly declared, “We refuse to be your mammies, nannies, aunties, uncles, girls, handmaidens any longer.” With compelling personal stories of the leaders and participants on the front lines, Household Workers Unite gives voice to the poor women of color whose dedicated struggle for higher wages, better working conditions, and respect on the job created a sustained political movement that endures today."